Adaptable pressure textile sensors based on a conductive polymer. (12th July 2018) - Tessarolo, Marta; Possanzini, Luca; Campari, Enrico Gianfranco; Bonfiglioli, Roberta; Violante, Francesco Saverio; Bonfiglio, Annalisa; Fraboni, Beatrice
Abstract: Recent studies in the field of safety in the workplace have focused on developing new sensors and procedures to detect and monitor body stress due to repeated or highly stressful movements that, in the long term, could lead to painful traumas or accidents. Today, the common method used to evaluate risk activities is based on evaluations that are subjective or supported by difficult and time-consuming video analysis. However, recent developments in wearable sensors, in particular pressure sensors, allow for innovative alternatives. The main requirements of wearable pressure sensors are good wearability, allowing natural movements and a sensor response in a broad range of pressure to allow a large variety of possible activities to be monitored. In this paper, we report on a new promising class of textile pressure sensors based on the employment of a conductive polymer that can be easily deposited directly on the fabric, for example, to fabricate sensorized gloves to monitor hand stress during manual activity. The main advantages of the proposed technology comprise the possibility of selectively tuning the pressure response range, adapting it to different applications by changing the formulation of the conductive polymer while leaving the same device architecture and structures. We deposit and characterize the active sensing layer, analyze the pressure sensor response and propose an interpretation of the obtained results based on piezoresistive phenomena. We identify three different contributions to the sensor output, related to the macroscale, microscale and nanoscale, respectively. Finally, we describe the production of sensorized textile gloves with fully textile pressure sensors that are comfortable, reproducible, low cost and easily tunable in pressure range response.